ASPEK YURIDIS SIMPANAN DAN PENITIPAN PADA BANK - Endang Retnowati (Perspektif, 2004)
Bank is a business entity that collects community funding in the form of deposit, and then distributes back to the community in the form of credit. The deposit with drawl should only be done due to specific term and condition. This agreement is made for the protection and the security of the customer and the bank it self.